2009
DOI: 10.1007/s11627-009-9197-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of enzymes and identification of stage-specific proteins in developing somatic embryos of chickpea (Cicer arietinum L.)

Abstract: Accumulation of proline, activities of peroxidase (POX), catalase (CAT), phenylalanine ammonia lyase (PAL) and malate dehydrogenase (MDH) were studied during different developmental stages of somatic embryos in chickpea. Callus cultures that did not form somatic embryos served as control. While increased levels of proline and POX activity were noticed in globular stages of embryos, CAT activity increased during early and late heart-shaped embryo formation indicating tissue-specific activation of these enzymes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It should be mentioned that increased somatic embryogenesis through proteins and amino acids is due to the fact that the compositions easily supply the source of nitrogen for the cell growth [35]. Proline plays an important role in somatic embryogenesis and stress conditions in plants [62]. For example, studies have shown that the proline-rich protein is required in the cell wall of Arabidopsis for correctly placing cell plate during cytokinesis process for embryos development.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that increased somatic embryogenesis through proteins and amino acids is due to the fact that the compositions easily supply the source of nitrogen for the cell growth [35]. Proline plays an important role in somatic embryogenesis and stress conditions in plants [62]. For example, studies have shown that the proline-rich protein is required in the cell wall of Arabidopsis for correctly placing cell plate during cytokinesis process for embryos development.…”
Section: Resultsmentioning
confidence: 99%
“…Free proline was suggested to act as an osmoticum, a nitrogen storage pool and source of NADP + , necessary for rapidly growing embryos. The mediation of the cellular redox potential that resulted from proline accumulation likely had a significant effect on the flux through redox-sensitive biochemical pathways like the pentose phosphate pathway [21].…”
Section: Induction Of Somatic Embryogenesismentioning
confidence: 99%
“…Nevertheless, molecular markers are relatively expensive in the equipment and reagents required, in typically well-established molecular laboratories. In contrast, biochemical markers based on proteins such as enzymes and storage proteins offer an alternative method involving cheaper and simpler protocols for crop breeding including wheat (Shewry & Halford, 2001; Ghanti et al, 2009; Al-Doss et al, 2010; Netsvetaev, Akinshina & Bondarenko, 2010; Hailegiorgis, Lee & Yun, 2017). Additionally, protein synthesis is encoded by genes, and modulation of gene expression in response to changes in the environment directly results in different levels of the corresponding proteins.…”
Section: Introductionmentioning
confidence: 99%